1988
DOI: 10.1002/1097-0142(19881015)62:8<1653::aid-cncr2820620833>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Non-hodgkin's lymphomas in turkey

Abstract: Between 1982 and 1986, 185 adult patients with non-Hodgkin's lymphoma (NHL) were studied at Cukurova University Hospital (CUH), Adana, Turkey. This constituted 13% of all malignant neoplasms diagnosed in the oncology clinic. The mean age for men was 45.5 years and 41 years for women. Fifty-four percent of the cases were nodal lymphoma and the remaining 46% were extranodal lymphoma. Sixty-six percent of the extranodal lymphoma cases were gastrointestinal lymphoma. The stomach was the most common localization (4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 21 publications
0
12
1
Order By: Relevance
“…When data of the studies performed in USA, Europe, and Asia, using Ann Arbor staging system, 45-54 % of NHL patients were at an advanced stage of their disease at the time of diagnosis [20][21][22][23]. In our study, 63.9% of our patients were at an advanced stage of their disease (stage 3-4) at the time of diagnosis which is higher than those reported in various literature studies.…”
Section: Discussioncontrasting
confidence: 55%
“…When data of the studies performed in USA, Europe, and Asia, using Ann Arbor staging system, 45-54 % of NHL patients were at an advanced stage of their disease at the time of diagnosis [20][21][22][23]. In our study, 63.9% of our patients were at an advanced stage of their disease (stage 3-4) at the time of diagnosis which is higher than those reported in various literature studies.…”
Section: Discussioncontrasting
confidence: 55%
“…Primary extranodal lymphoma constitutes 25% of the NHL cases in North America and up to 50% in parts of Europe, Turkey, and Middle Eastern countries 3-5. The incidence of GI lymphoma is higher in Eastern Countries than Western Countries 4-6. High grade histopathologic types of gastric lymphomas are higher in Turkey and Middle East Countries than Western Countries 3-6…”
Section: Introductionmentioning
confidence: 99%
“…Two studies of gastrointestinal lymphoma patients from Ç ukurova University 16,17 reported gastric lymphomas to be the major form of gastrointestinal lymphoma whereas a previous report from our center 18 and another one from Ankara University found intestinal lymphomas to be the most common gastrointestinal lymphomas. This issue was not addressed in this study, and sufficient epidemiologic data are lacking at the moment to draw conclusions.…”
Section: Discussionmentioning
confidence: 79%
“…[1][2][3] One striking difference in this analysis of 78 gastric lymphoma patients from Turkey is the notably younger age distribution that also was reported in other Turkish series. [15][16][17][18][19] Gastric lymphoma is a disease occurring later in life. Most of the cases are diagnosed after the age of 50 years, with a mean age older than 55 in most published series.…”
Section: Discussionmentioning
confidence: 99%